2021
DOI: 10.1021/acsami.1c03717
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium Metal–Organic Frameworks Integrating Chloride Ions for Ammonia Capture and/or Chemical Separation

Abstract: Ammonia capture by porous materials is relevant to protection of humans from chemical threats, while ammonia separation may be relevant to its isolation and use following generation by emerging electrochemical schemes. Our previous work described both reversible and irreversible interactions of ammonia with the metal–organic framework (MOF) material, NU-1000, following thermal treatment at either 120 or 300 °C. In the present work, we have examined NU-1000-Cl, a variant that features a modified node structure–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 53 publications
(77 reference statements)
0
25
0
Order By: Relevance
“…MOFs, consisting of metal-based nodes connected by polytopic organic linkers, are a class of hybrid materials characterized by high tunability, crystallinity, , porosity, , multifunctionality, and site uniformity. , Many present readily accessible catalytic sites. , Zirconium-based MOFs have shown outstanding chemical (between pH ∼1–11) and thermal (up to 500 °C) stability. , Specifically, Zr 6 -based MOFs ( e.g. , NU-1000, UiO-66, and MOF-808) featuring reactive or displaceable −OH and −OH 2 ligands and Zr-OH-Zr linkages, which are structurally reminiscent of the Zn-OH-Zn-containing active site of PTE, show remarkable catalytic activity for hydrolysis of CWAs, such as GB and GD, and their simulants, such as methyl paraoxon (Figure ), also known as dimethyl-4-nitrophenyl phosphate (DMNP). ,,, One metal in the M-OH-M site coordinately binds to the double-bonded oxygen, thereby weakening the PO bond and indirectly weakening (activating) the targeted P–X bond.…”
Section: Introductionmentioning
confidence: 99%
“…MOFs, consisting of metal-based nodes connected by polytopic organic linkers, are a class of hybrid materials characterized by high tunability, crystallinity, , porosity, , multifunctionality, and site uniformity. , Many present readily accessible catalytic sites. , Zirconium-based MOFs have shown outstanding chemical (between pH ∼1–11) and thermal (up to 500 °C) stability. , Specifically, Zr 6 -based MOFs ( e.g. , NU-1000, UiO-66, and MOF-808) featuring reactive or displaceable −OH and −OH 2 ligands and Zr-OH-Zr linkages, which are structurally reminiscent of the Zn-OH-Zn-containing active site of PTE, show remarkable catalytic activity for hydrolysis of CWAs, such as GB and GD, and their simulants, such as methyl paraoxon (Figure ), also known as dimethyl-4-nitrophenyl phosphate (DMNP). ,,, One metal in the M-OH-M site coordinately binds to the double-bonded oxygen, thereby weakening the PO bond and indirectly weakening (activating) the targeted P–X bond.…”
Section: Introductionmentioning
confidence: 99%
“…21 The XPS data supported the above FT-IR results and further explained why ammonia could not be completely desorbed. 82 These results reveal that the highly efficient adsorption of NH 3 was mainly attributed to the NH 3 coordination to Zn cation and the hydrogen-bonding interaction of NH 3 with Cl of [C 1 NH 3 ][Zn 3 Cl 7 ], although FDU-12 also had a minor contribution to ammonia adsorption.…”
Section: ■ Results and Discussionmentioning
confidence: 85%
“…Our previous studies have shown that the aqua/hydroxo ligands in NU-1000 can behave as displaceable site-holders for graing non-structural ligands, 37,38 as reactive sites for immobilizing metal cations, [39][40][41][42] and as charge-compensating hydrogen bonding sites for noncovalently immobilizing halide ions. 14,43 Each of three candidate nonstructural ligands, acetylacetonate (Acac À ), 1,1,1-tri-uoroacetylacetonate (TFacac À ), or hexauoroacetylacetonate (Facac À ) was graed, via SALI (solvent-assisted ligand incorporation), onto Zr 6 -oxy nodes (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%